Improving the Art-Pedagogical Educational Process for Students of Higher Education Institutions (Journal of Pedagogical Inventions and Practices, 2026)
This article examines the theoretical and methodological foundations for improving the artpedagogical educational process for students of higher education institutions. In modern higher education, art pedagogy is considered not only as a means of developing artistic skills, but also as an effective pedagogical mechanism for shaping students’ creativity, aesthetic worldview, emotional intelligence, communicative competence and professional culture. The article analyzes the importance of integrating artbased methods, interactive technologies, project activities and reflective learning into the educational process. Special attention is paid to the role of the teacher, the organization of creative learning environments, and the development of students’ independent artistic thinking. The study argues that the modernization of art-pedagogical education requires a systematic approach based on national cultural values, global educational experience and innovative pedagogical technologies